(untitled) (Communications in Computational Physics, 2018)
Combining asymptotic analysis and weighted L_2 stability estimates, the convergence of lattice Boltzmann methods for the approximation of 1D convection-diffusion-reaction equations is proved. Unlike previous approaches, the proof does not require transformations to equivalent macroscopic equations.